ORIENTASI PASAR PADA UD. BINTANG LIMA PRODUK KACANG TELUR DI KOTA TOMOHON - Steriany Maria Tulenan; Leonardus R. Rengkung; Joachim N.K. Dumais (AGRI-SOSIOEKONOMI, 2016)
The objective of this research is to determine the orientation of the market (customer orientation, competitor orientation and coordination between functions). This research conducted for three months, since February to April 2016. The data used in this research is the primary data taken using a survey method using a questionnaire that by distributing questionnaires to employees and manager. A questionnaire was used to determine the customer orientation, competitor orientation and coordination between functions. Based on the results of research conducted at the Five Star UD, it can be concluded that Five Star has captured the market orientation that is good with market orientation value of 64.31 persent. UD's market orientation on customer orientation is said to be good in that understanding of these UD on the wishes of customers, know what customers want, satisfaction and create value for customers. In the competitor orientation, this UD could respond to acts of competitors, competitive advantage to seize opportunities, and try to improve and find a strategy to fight its competitors. While in the coordination between functions, workers has contributed to the strategy of Five Star UD and the customer value creation, mutual cooperation among workers, and has understood the needs of customers so as to create satisfaction for its customers.